THE USE OF GOOGLE TRANSLATE IN ARABIC LANGUAGE LEARNING AMONG GRADE X STUDENTS AT MAS MUTIARA AULIA MEDAN - Mutia Rakhma Anwar; Zulfahmi Lubis (Al Ibrah: Journal of Arabic Language Education, 2026)
This study aims to describe the use of Google Translate in Arabic language learning among Grade X students at Madrasah Aliyah Mutiara Auliya Medan, to analyze students' perceptions of its effectiveness as an assistive medium, and to examine its contribution to the development of four language skills namely listening, speaking, reading, and writing. This study employs a qualitative approach with a descriptive method. Data were collected through passive participatory observation, semi-structured in-depth interviews with six students and one Arabic language teacher, and documentation. Data analysis used the interactive model of Miles and Huberman, comprising data reduction, data presentation, and conclusion drawing. Data validity was tested through source triangulation and technique triangulation. The findings indicate that: (1) students use Google Translate intensively outside the classroom with an instant-use pattern of translating full sentences or paragraphs; (2) students perceive Google Translate as effective in helping them understand Arabic vocabulary and texts quickly, although translation results are not always accurate, particularly in grammatical and contextual aspects; (3) Google Translate contributes most to reading skills and slightly to writing skills, but its impact on listening and speaking skills is very limited. The study concludes that the use of Google Translate potentially creates dependency that may hinder the development of students' critical thinking and independent Arabic language learning if not wisely guided by teachers.